Expressive Speech Acts at Ages 18+ in Auction Place (TPI) Community - Reisti Shintiana Putri; Veronica Veronica; Ressty Putri Ariyati; Rego Yasendalika; Ike Revita (Vivid: Journal of Language and Literature, 2020)
This study aims to describe the  forms of expressive speech act uttered by adults in TPI in Pesisir Selatan Regency, Sumatera Barat. This  is a descriptive qualitative research. The data are any  utterances which contain expressive speech acts of adult in TPI Pesisir Selatan.  The analysis is done by using speech acts theory proposed by Searle. Data source of this research is Adult in TPI. In this research, the researcher used observational method because the data are in the form of spoken language that obtained in a Adult in TPI. Thus this research used notetaking technique in collecting expressive speech act. The research findings show that there are ten kinds of expressive speech act in adults in TPI, namely apology, thanks, sympathy, attitudes, expressing greeting, wishing, expressing joy, expressing pain, expressing like, and expressing dislikes.